Exploring the opportunities of the emojis in brand communication: The case of the beer industry - Casado-Molina, Ana María; Rojas-de-Gracia, María Mercedes; Alarcón-Urbistondo, María del Pilar; Romero Charneco, María (SAGE journals, 2022)
This study shows that emojis are a significant element in brand communications, which still requires attention from researchers. Specifically, it describes the use of emojis by the four companies with the largest audiences on Twitter in the Spanish beer industry. Through a correspondence analysis, we found that those emojis were not a mere occasional resource within a message but rather a differentiating element for brand positioning. Likewise, we analyzed the existing relationship between the way in which they were used and the engagement generated. In this regard, we concluded that communications using emojis aimed at customer service and care, as well as those used in positive contexts and for emphasis, were the ones related to higher user engagement. We discuss herein the practical implications of these findings for businesses. Este estudio muestra que los emojis son un elemento significativo en la comunicación de marca que aún requiere la atención de los investigadores. En concreto, se describe el uso de emojis por parte de las cuatro empresas con mayor audiencia en Twitter en el sector cervecero español. A través de un análisis de correspondencias, se encontró que dichos emojis no eran un mero recurso ocasional dentro de un mensaje sino un elemento diferenciador para el posicionamiento de marca. Asimismo, se analizó la relación existente entre la forma en que se utilizaban y el engagement generado. En este sentido, se concluyó que las comunicaciones con emojis orientadas a la atención y servicio al cliente, así como las utilizadas en contextos positivos y de énfasis, eran las relacionadas con un mayor engagement de los usuarios. Inspirados en estos resultados se discuten las implicaciones prácticas para las empresas.
Keywords: Medios de comunicación social; Marketing en Internet; Emojis; Marca comercial; Comunicación de marcas comerciales; Engagement; Conversación social; Marketing conversacional; Marketing digital; Digital communications; Social conversations; Brand communications